PENGGUNAAN “AUTOMATIC FEEDER” PADA PENDEDERAN IKAN KERAPU TIKUS (Cromileptes altivelis) - Wiwie Soemarjati; Veni Damayati; Yani Lestari; Mizab Asdari (Faculty of Science and Technology University Ibrahimy, 2013)
Seeds of humpback grouper are often nursery is the size of 3 cm, to feed for nursery use artificial feed or pellets. Feed pellets are in great demand by employers nursery, this is because the artificial feed (pellets) nutritionally complete, easy to obtain, not depending on the season, easy in giving, does not require much effort to chop up trash fish and does not contaminate the media maintenance. Obstacles often faced in the nursery humpback grouper is an artificial feeding system gradually by feeding manually little by little until the fish are fed. Feeding system requires a lot of effort and a long time, making it less practical. The purpose of this engineering is to get the technique of feeding